PENGEMBANGAN BAHAN AJAR BERMUATAN KEARIFAN LOKAL DAERAH PONTIANAK PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR NEGERI 35 PONTIANAK SELATAN - Nur Affni; Agung Hartoyo; Kartono (STKIP Subang, 2026)
This research is motivated by the teaching materials on the material of plane figures that are still less interesting, lack illustrations, and have not linked the material to students' lives so that students have difficulty understanding the concept. This study aims to develop teaching materials containing local wisdom of the Pontianak region on the material of plane figures of grade IV of SD Negeri 35 South Pontianak that are suitable for use in learning. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, and development. Data were collected through interviews and questionnaires, then analyzed qualitatively and quantitatively. The results of the study showed that at the analysis stage, it was found that the teaching materials did not meet students' needs and did not support conceptual understanding. At the design stage, a teaching material design was produced that was arranged in stages, equipped with illustrations, and linked the material to Pontianak's local wisdom. At the development stage, the resulting teaching materials were categorized as very valid, with a percentage of material aspects of 87%, media 87%, and language 92%. The results of the socialization showed a response from teachers of 86% and students of 86% with a very good category. Thus, the developed teaching materials are declared suitable for use to support more contextual learning and help students' understanding.